Does momentum exist in elite handball? - Mortimer, Philip; Burt, W. Edward (International journal of performance analysis in sport, 2014)
The theory of momentum is contentious within performance analysis in sport and has been subject to much academic investigation; with many researchers exploring the scale of its existence. Within handball, previous research has focused predominantly on psychological momentum with no statistical analysis of behavioural momentum, as found in research into basketball and other sports. In this study, a method derived from Taylor and Demick (1994) was used to investigate the existence and effect of behavioural momentum in 45 elite handball matches. Results highlighted momentum as being present within elite handball, and having a positive effect on match outcome in 86% of the matches analysed. Further assessment of the results indicated turnovers in possession, at stage two of the three-stage momentum model, to be a key performance indicator. It is hoped this study can be used to develop future research that incorporates a more complex analysis of the existence and effect of momentum in elite sport.